2017
DOI: 10.1371/journal.pone.0183305
|View full text |Cite|
|
Sign up to set email alerts
|

Timing and rate of spheno-occipital synchondrosis closure and its relationship to puberty

Abstract: ObjectivesThis study examines the relationship between spheno-occipital synchondrosis (SOS) closure and puberty onset in a modern American population. It also investigates the timing and the rate of SOS closure in males and females.Materials and methodsThe sample includes cross-sectional and longitudinal 3D Cone Beam Computed Tomography (CBCT) scans of 741 individuals (361 males and 380 females) aged 6–20 years. Each CBCT scan is visualized in the mid-sagittal plane, and the spheno-occipital synchondrosis (SOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 35 publications
6
42
0
2
Order By: Relevance
“…Its relationship to puberty has been described in a recent study and proposed on computed tomography. Stages 0 and 1 were considered pre-pubertal and stages 2 and 3 post-pubertal (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its relationship to puberty has been described in a recent study and proposed on computed tomography. Stages 0 and 1 were considered pre-pubertal and stages 2 and 3 post-pubertal (11).…”
Section: Methodsmentioning
confidence: 99%
“…Staging system for pubertal status based on sphenooccipital synchondrosis closure on imaging (adapted from Alhazmi et al(11)). …”
mentioning
confidence: 99%
“…shown that SOS maintains a cartilaginous separation of both bones for up to about 18 years (5,8). Radiological and morphological examinations, however, showed that bony bridges between the two bones appear earlier (7)(8)(9)(10)(11). It is assumed that bony bridging results in loss or limited elasticity of the growth plate so that the bone growth on this joint ceases with the first bridging (15).…”
Section: Development and Fusion Of Sos Morphological Studies Havementioning
confidence: 99%
“…Sphenoocipital synchondrosis (SOS) forms the cartilaginous connection between the sphenoid and the basi-occipital bone (1)(2)(3). This synchondrosis is considered an important growth zone of the skull base and usually ossifies towards the end of the second decade of life (4)(5)(6)(7)(8)(9)(10)(11). Residues of SOS can be demonstrated on radiological sectional images of complete ossified bones in young adults, but also in later phases of life, even in old age (12).…”
mentioning
confidence: 99%
“…In combination, these features indicate a developmental age of around 15–18 years (Al Qahtani et al 2014; Alhazmi et al . 2017).
Figure 3.Occlusal view of the maxilla, showing the erupted left first molar; the third molars are visible in their crypts (photograph by G. Cole).
…”
Section: Osteological Assessment: Age At Death Biological Sex and Evmentioning
confidence: 99%